Refractory optic perineuritis related to granulomatosis with polyangiitis treated with intensive immunosuppressive therapy combined with plasma exchange. (2nd January 2020) - Mitsuhashi, Masaki; Yoshimi, Ryusuke; Kishimoto, Daiga; Hidekawa, Chiharu; Iizuka, Yuki; Sakurai, Natsuki; Kamiyama, Reikou; Kirino, Yohei; Kondo, Yukiho; Mizuki, Nobuhisa; Nakajima, Hideaki
Abstract: Optic perineuritis (OPN), which is an inflammatory disorder affecting the optic nerve sheath, is one of the rare complications in granulomatosis with polyangiitis (GPA). Although several groups have reported that immunosuppressive therapies are generally effective against GPA-associated OPN, so far, there is little information as to other options for refractory cases. Here we demonstrate a case of GPA-associated OPN, which is refractory to potent immunosuppressive therapy including high-dose glucocorticoid, intravenous cyclophosphamide and rituximab therapy, and effective application of therapeutic plasma exchange. We also report here that CSF IL-6 levels may serve as a new biomarker for GPA-associated OPN.